2017
DOI: 10.1155/2017/8618340
|View full text |Cite
|
Sign up to set email alerts
|

First-Principles Study of Properties of Alpha Uranium Crystal and Seven Alpha Uranium Surfaces

Abstract: First-principles calculation based on the GGA methods has been applied to the prediction of the properties of bulk -uranium and seven -uranium surfaces. The number of layers in the slab has great effects on the simulated surface properties. The predicted surface properties are trustworthy when the slab number is nine or more. The surface energies of the seven low index uranium surfaces are in the range from 1.756 to 2.151 J/m 2 . The hybrid between the 5 orbital and 6 orbital also has somewhat impacts on the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…Here, we chose the (001) surface as this is the most stable α-U facet. The experimental surface energy of α-U is 1.828 J/m 2 ; however, this value corresponds to an isotropic crystalline structure of the metal or an average value of different surfaces . Since the (001) facet has the lowest energy, it would be the most abundant surface in the uranium crystalline material.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, we chose the (001) surface as this is the most stable α-U facet. The experimental surface energy of α-U is 1.828 J/m 2 ; however, this value corresponds to an isotropic crystalline structure of the metal or an average value of different surfaces . Since the (001) facet has the lowest energy, it would be the most abundant surface in the uranium crystalline material.…”
Section: Resultsmentioning
confidence: 99%
“…The experimental surface energy of α-U is 1.828 J/m 2 ; however, this value corresponds to an isotropic crystalline structure of the metal or an average value of different surfaces. 19 Since the (001) facet has the lowest energy, it would be the most abundant surface in the uranium crystalline material. As presented in Table 2, the descending order of the surface energy for various functionals is RPBE_D3BJ > PBE_D3BJ > PBEsol > PBE > SCAN.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the calculations were performed with the Vienna Ab Initio Simulation Package (VASP) version 5.4.4. , The projector-augmented wave (PAW) method and Perdew–Burke–Ernzerhof (PBE) exchange-correlation functional were employed . Previous studies have demonstrated that GGA functionals could accurately describe the electronic structure of 5f metals including U and plutonium (Pu). It has also been shown that DFT+ U calculations with Hubbard correction on 5f orbitals of U significantly overestimate the atomic volume of U metal and alloys . Therefore, we selected the PBE functional in this work.…”
Section: Methodsmentioning
confidence: 99%
“…To this end, we have employed in this study a combination of ab initio density functional theory (DFT) calculations and kinetic Monte Carlo (KMC) simulations to predict the bulk diffusivity of Nd through a-U, fully taking into account the effect of radiation enhanced diffusion. We have further considered the migration of Nd adatoms on the a-U (001) surface, which is the most stable (i.e., having the lowest surface energy) among seven low index surfaces considered by Huang and Ju [7]. Importantly, the temperature-dependent bulk and surface diffusivities of Nd in a-U calculated here using lower length scale simulations, together with the diffusion coefficients of Nd in liquid Na/Cs from Li et al [4,5], can be used to parameterize mesoscale phase-field simulations using the MARMOT code [8] to determine the effective diffusivity of Nd through a-U fuel with a porous microstructure.…”
Section: Introductionmentioning
confidence: 99%